Unveiling the complex extra‐oral colonization pathways and pathogenic mechanisms of Fusobacterium nucleatum, a heterogeneous oral pathogen - Zhiwei Guan; Houbao Qi; Qiang Feng (View)
Abstract Fusobacterium nucleatum is a heterogeneous bacterium that includes four subspecies. It is not only an opportunistic pathogen of periodontitis but also can be frequently detected at the lesion sites of various systemic diseases. Extensive research has underscored the significant involvement of F. nucleatum in the onset, progression, and therapeutic responses of numerous oral and systematic diseases. Given its convenient isolation from lesions, feasibility to cultivate in vitro, and diverse pathogenic pathways, F. nucleatum has emerged as a “model species” for elucidating the effects of oral pathogens on systemic human health. Here, we begin by introducing the taxonomic characteristics of F. nucleatum. Next, we explore F. nucleatum’s ability to adhere to and invade host cells, which serves as a critical prerequisite for its pathogenicity. Subsequently, we analyze the pathways through which F. nucleatum achieves ectopic colonization, revealing how it establishes infections in non‐oral sites such as the intestine and reproductive tract. Furthermore, we elaborate on F. nucleatum’s pathogenic mechanisms, particularly in cardiovascular diseases, adverse pregnancy outcomes, and cancer, focusing on how it modulates host immune responses through diverse virulence factors and signaling pathways. Finally, we summarize the advances in understanding the regulatory mechanisms underlying F. nucleatum’s pathogenesis. We aim to provide a theoretical foundation for developing clinical interventions targeting F. nucleatum and to offer insights and directions for future investigations into the pathogenesis of oral pathogens in systemic diseases.